Navigating Calcified Challenges: Guided Endodontic Treatment of a Maxillary Central Incisor - Saide Nabavi; Sara Navabi; Iman Shiezadeh; SeyedehZahra JamaliMotlagh (Clinical Case Reports)
ABSTRACT This case report details the guided endodontic treatment of a calcified maxillary central incisor in a 47‐year‐old patient with a history of trauma. Traditional methods pose challenges in managing pulp canal obliteration (PCO) due to the risk of perforation and excessive dentin removal. Guided endodontics, integrating cone‐beam computed tomography (CBCT) and intraoral scanning, was employed to design a 3D‐printed guide, allowing precise, minimally invasive access to the obliterated canal. A customized guide facilitated accurate drilling with minimal tooth structure loss. The canal was successfully negotiated, cleaned, shaped, and obturated. Posttreatment, the tooth underwent internal bleaching to address discoloration. At the 18‐month follow‐up, the tooth was asymptomatic, functional, and showed complete periapical healing. This report highlights the efficacy of guided endodontics in managing calcified canals, emphasizing its precision, reduced procedural risks, and preservation of dental structure. While challenges such as guide accuracy and workflow complexity remain, advances in digital technology continue to enhance clinical outcomes in endodontics.